Circulating adiponectin as a biomarker in renal cell carcinoma: a systematic review and meta-analysis - Yap, Ning Yi; Yap, Foo Ngan; Perumal, Komathi; Rajandram, Retnagowri (Taylor & Francis, 2019)
Context: Metabolic imbalance in renal cell carcinoma (RCC) can lead to abnormal adiponectin levels. Objective: To evaluate circulating adiponectin as a detection or predictive marker for RCC. Methods: A comprehensive literature search and meta-analysis was performed on studies reporting circulating adiponectin levels and RCC. The meta-analysis was performed using RevMan. Results: Seven studies compared the circulating adiponection levels between RCC cases and controls. Adiponectin level was significantly lower in RCC cases compared to controls at pre-diagnosis and pre-operative time-points. RCC stage, grade and subtype did not affect adiponectin levels. Conclusion: Low circulating adiponectin could be a predictive or risk factor for RCC. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.